Economics of rural infrastructure : evaluating the provision of transport and electricity in Peru : 1. Electoral cycles and renegotiation of transport infrastructure concession contracts ; 2. Impact of rural electrification on education, a case study from Peru ; 3. Roads and agriculture : impacts of connectivity in Peru - Aguirre Montoya, Julio César (2016)
Fil: Aguirre Montoya, Julio César. Universidad de San Andrés. Departamento de Economía; Argentina.